PEMODELAN SPASIAL PRODUKSI IKAN PADA INDUSTRI BUDIDAYA PERIKANAN DI KOTA CILEGON - Atia Sonda; Faula Arina; Ade Sri Mariawati; Asep Ridwan; Dyah Lintang Trenggonowati (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
The aquaculture industry in Cilegon City is fairly substantial. In the year 2020, 230.09 tons of farmed fish were produced. In Cilegon City, fish production statistics is often used for each sub-district. So far, no research has been undertaken to examine the dependency of fish output from one district to the next. Spatial modeling is used to examine the spatial correlation of fish production data in each sub-district, making it easier to characterize observations in a sub-district and their relationships with other sub-districts. A semivariogram model was fitted using the fish production data, and it was discovered that fish production in the city of Cilegon followed the cubic model with model parameters C = 2.9891 and range a = 5.28. Furthermore, using this spatial model, assessment of fish production in a location, in this example Cilegon City, can be carried out in further research in an effort to see food security.